Examination of Lintner’s and Brittain’s Dividend Models: Evidence from Indian Public Manufacturing Companies - Dr. Jasvir S. Sura; Dr. Anju Lather; Gourav (Innovative Research Thoughts, 2023)
Dividend policy determines whether earnings are paid to stockholders or reinvested in the company, and it has always been a topic of discussion among shareholders and researchers. Companies' Management also prefers to maintain a consistent dividend policy because any change in dividend policy signals a change in the company's future earnings. As a result, an attempt has been made to justify whether Lintner's (1956) and Brittain's (1964) cash flow models and their extension of dividend behaviour are suitable for Indian corporations. Therefore, the prime objective of the paper is to test the validity of the models; panel data analysis was performed on Indian public manufacturing companies from 2001 to 2020. The results were found to be similar to the Linter model as well as the Britain cash flow model. However, the extended Model's findings differ from those of the two models. The study also revealed that Indian companies primarily base their dividend policies on previous dividends and that sample Indian manufacturing companies adhere to a consistent and smooth dividend policy.